Análise comparativa dos frameworks de certificação no setor mineral: uma revisão sistemática dos indicadores de sustentabilidade - Vilas Boas, Marcela Poletto (Universidade Federal de São Carlos, 2026)
Mining is an ancient activity essential for economic development, but its environmental and social impacts require the implementation of sustainable practices. This project aims to comparatively analyze global voluntary certification frameworks in the mining sector, focusing on the sustainability indicators adopted by certified mining companies. The goal of the research is to examine the indicators of certification standards adopted in mining and the methods used. The research, of a qualitativa nature, will be conducted through a comprehensive literature review and analysis of public audit and sustainability reports from major mining companies, such as Vale, AngloAmerican, among others. Indicators such as water consumption, greenhouse gas emissions, biodiversity impact, and worker health and safety will be compared with criteria established by frameworks like the Initiative for Responsible Mining Assurance (IRMA), the International Council on Mining and Metals (ICMM), and the Global Reporting Initiative (GRI). Expected results include a detailed understanding of the effectiveness of the frameworks, gaps in the indicators, and proposals for improving sustainable practices in the sector. This study could serve as a guide for companies and certifiers, promoting greater environmental and social responsibility in the mining sector.
Comparative analysis of certification frameworks in the mining sector: a systematic review of sustainability indicators
Keywords: Certificação ambiental; Diferenciação; Convergência; Commodities minerais; Environmental certification; Differentiation; Convergente; Mineral Commodities; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIAS AGRARIA E DOS RECURSOS NATURAIS; ENGENHARIAS::ENGENHARIA DE MINAS::TRATAMENTO DE MINERIOS; 7. Energia limpa e acessível; 17. Parcerias e Meios de Implementação; 9. Indústria, Inovação e Infraestrutura; 13. Ação contra a Mudança Global do Clima; 15. Vida Terrestre